Trends of underweight, overweight, and obesity among older adults in China from 2008 to 2018: a national observational survey - Dina Jiesisibieke; Yuting Feng; Zhu Liduzi Jiesisibieke; Jue Liu; Liyuan Tao (BMC Public Health, 2023)
Abstract Objective This study aims to investigate the 10-year trends and disparities in underweight, overweight, and obesity among older adults aged 65 years and older in China from 2008 to 2018. Methods We used four waves (2008, 2011, 2014, and 2018) of data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), a national community-based cross-sectional survey conducted every 2–3 years. Body weight and height were measured by trained assessors following standardized procedures. BMI was calculated and divided into underweight (< 18.5 kg/m2), normal (18.5–24.9 kg/m2), overweight (25.0-29.9 kg/m2), obese (≥ 30.0 kg/m2) according to WHO reference. Multinomial logistic regression models were used to examine factors related with abnormal BMI groups, after adjusting for potential confounders. Results Among 46,543 older adults in China, the prevalence rates of underweight decreased with each survey year from 2008 to 2018, declining from 20.05 to 7.87% (p < 0.001). In contrast, the prevalence rates of overweight and obesity showed an increasing trend (all p < 0.001). Specifically, the prevalence of overweight rose from 12.82% to 2008 to 28.45% in 2018, and the prevalence of obesity increased from 1.62% to 2008 to 4.95% in 2018. In the multinomial logistic regression model, survey year, gender, residence, marital status, economic status, numbers of chronic diseases, smoking status, sleep quality, and functional disability were factors related with obesity. Conclusion The prevalence rates of overweight and obesity were increasing while the prevalence of underweight and normal weight significantly decreased from 2008 to 2018 among older adults in China, which poses a huge challenge for chronic disease. There is an urgent need for intervention policy planning and early prevention of abnormal body weight for the preparation of an aging society.